Plan integral de desechos de la unidad de atención odontológica, Universidad Nacional de Chimborazo, 2019 - Caterine Elizabeth, Chacha Sinaluisa (2021)
ABSTRACT . This study aimed to propose an integral waste plan for UNACH's dental care unit under the guidelines of the MSP (Public Health Ministry). To achieve this goal, a survey was devised for students taking clinic I, II, III and IV classes. Data processing showed a level an adequate and moderately adequate treatment of waste, regarding the primary storage of waste, data suggested it was frequent and adequately frequent adequate. Finally, students indicated that they know how to differentiate waste properly. As for the existence of a comprehensive waste plan, 41.70% said they do not know or are unaware of its existence and 39.80% said they know or are aware of a waste plan. The waste that is most frequently produced in the clinics corresponds to the infectious biological type and to sharpen tools. In regard to the knowledge that they have about the risks derived from the incorrect management, there are the physical injuries, cuts and needle lesions, 83% and the infections with: Hepatitis B, Hepatitis C, HIV, 81% considered as high risk. Based on the results in this study and considering the importance of managing a comprehensive waste plan, this project considers the "Comprehensive Waste Plan of the dental care unit" as an alternative by adopting appropriate implementation mechanisms applied in the field of dental clinics as a contribution to the development of an adequate clinical exercise contributing adequately to the biosafety elements. Keywords: comprehensive plan, waste, dental care unit. Reviewed by: Mgs. Adriana Cundar Ruano Ph.D. ENGLISH PROFESSOR c.c. 0603017708